This lullaby a novel - Dessen, Sarah (New York Viking, 2002)
Raised by a mother who has had five husbands, eighteen-year-old Remy believes in short-term, no-commitment relationships until she meets Dexter, a rock band musician
1
Keywords: Dating (Social customs) -- Fiction; Interpersonal relations -- Fiction; Mothers and daughters -- Fiction; Musicians -- Fiction; Rock groups -- Fiction